Percutaneous dilatational tracheotomy in high-risk ICU patients - Lüsebrink, Enzo; Preusch, Michael (Annals of intensive care, 2021)
Percutaneous dilatational tracheotomy (PDT) has become an established procedure in intensive care units (ICU). However, the safety of this method has been under debate given the growing number of critically ill patients with high bleeding risk receiving anticoagulation, dual antiplatelet therapy (DAPT) or even a combination of both, i.e. triple therapy. Therefore, the purpose of this study, including such a high proportion of patients on antithrombotic therapy, was to investigate whether PDT in high-risk ICU patients is associated with elevated procedural complications and to analyse the risk factors for bleeding occurring during and after PDT.
Gesehen am 13.10.2021
PDT Investigator Group: Stefan Kääb, Stefan Brunner, Mathias Orban, Tobias Petzold, Saliha Kehar, Sara Würbel, Hans-Joachim Stemmler, Leonhard Binzenhöfer, Jan Kleeberger, Antonia Kellnar